Physics of the Permanent Cavity of the Firearm Wound - Emad Eldieb (Forensic Science Today - Peertechz Publications, 2015)
In this paper we would put a mathematic relation between the displacement(x2 ) of penetration of the lunched bullet inside the victim and the displacement(x1 ) in air before impact. The cardinal achievement of the article is that we use the physical definition of the inertial own mass of the matter as defined in the paper published by the author in 2014 under the title; physics of the giant atom [5].  From the definition we can state that if a projectile stroke a defined object with a force more than the binding force between its physical units (like macromolecules of the soft tissue) then the localized stroke zone would lose its physical relative inertia of the mother object and would be related to the inertial mass of the striking projectile in the form of conservation of kinetic energy as;  Ep - Eb = (m + δm) v2 Where v is the velocity after strike and the subscripts p and b means projectile and binding respectively and where m and δm means mass of the projectile and the incremental mass of the stroked zone respectively.  Since the tissue has some degree of elasticity and consequently each type of tissue has defined tensile strength and defined ultimate elongation, so the dot product of these physical quantities gives the defined toughness energy density of the tissue. The cardinal idea of our work is that: since toughness energy brings each incremental section area (of an elastic rode) in ultimate elongation meaning that offering each section enough energy to break, simultaneously the bullet throughout its pass brings each cross section of the tissue at break.  This means that the energy lost to do cavitations is equivalent to the toughness energy density times the volume of the permanent cavitations. This means that the bullet throughout its pass succeeds to bring the successive section areas of the tissue at break but without elongation. Since we have two unknowns; the stoppage energy of the bullet inside the victim and the displacement before striking the body, so we would divide our work into two indistinctive sections: where in each one we would put an equation to relate each unknown with the other so the two equations would solve the problem and finally we can define the displacement before impact.